Is there a tape recorder in your head? How the brain stores and retrieves musical melodies - Rauschecker, Josef P. (Frontiers in Systems Neuroscience, 2014)
Music consists of strings of sound that vary over time. Technical devices, such as tape recorders, store musical melodies by transcribing event times of temporal sequences into consecutive locations on the storage medium. Playback occurs by reading out the stored information in the same sequence. However, it is unclear how the brain stores and retrieves auditory sequences. Neurons in the anterior lateral belt of auditory cortex are sensitive to the combination of sound features in time, but the integration time of these neurons is not sufficient to store longer sequences that stretch over several seconds, minutes or more. Functional imaging studies in humans provide evidence that music is stored instead within the auditory dorsal stream, including premotor and prefrontal areas. In monkeys, these areas are the substrate for learning of motor sequences. It appears, therefore, that the auditory dorsal stream transforms musical into motor sequence information and vice versa, realizing what are known as forward and inverse models. The basal ganglia and the cerebellum are involved in setting up the sensorimotor associations, translating timing information into spatial codes and back again.